Oxidation Processes of Combined Meat Systems with Poultry Meat and Flaxseed Flour - Gurinovich G.; Sannikov P.; Patrakova I. (Техника и технология пищевых производств)
It is a modern trend to use various types of plant materials in food formulae. Such an approach improves the technological properties of meat and prolongs the shelf-life of finished products. Flaxseed flour is one of the most advantageous plant crops with antioxidant properties. The present research features the effect of flaxseed flour on the oxidative processes of combined minced poultry and the synergistic effect of flaxseed flour with antioxidant additives, including ascorbic acid (0.05%), sodium citrate (0.03%), and α-tocopherol (0.02%). The paper presents an experimental research on oxidation of lipid and protein fractions of minced meat in semi- smoked sausages according to the amount of flaxseed flour that was introduced in the formula alone or in combination with various additives of antioxidant action. When 5–10% of hydrated flaxseed flour was added into the minced meat, it resulted in an inhibition of lipid oxidation. In the combined minced meat at a storage temperature of 0–4°C, the content of secondary oxidation products remained within the acceptable limits defined by safety standards (2 mg MA/kg) up to 4 days. However, this level was exceeded after only 3 days of storage in the control sample. The experiment made it possible to define the indicators characterizing the development of oxidation processes of the color-forming proteins of minced meat with the addition of flaxseed flour, including the amount of common pigments,metpigments, nitric oxide pigments, and heme iron. The indicators proved the stabilizing effect of flax flour on the coloration of the combined minced meat systems. From the point of view of inhibiting the oxidation of the lipid and protein components, the maximum synergistic effect was provided by two combinations: 1) flaxseed flour and sodium citrate; 2) flaxseed flour, sodium citrate, and α-tocopherol.